Impact of Interleukin-10 Promoter Region Polymorphisms on Recurrent Miscarriage: A Case–Control Approach - Neha Sudhir; Mandeep Kaur; Sukhjashanpreet Singh; Archana Beri; Tajinder Kaur; Anupam Kaur (Journal of Human Reproductive Sciences)
Background: Recurrent miscarriage (RM), defined as two or more consecutive miscarriages prior to the 20th week of gestation is characterised by multifactorial aetiology. The prevalence of RM varies from 0.8% to 13.5% amongst women of reproductive age. The aetiological basis of RM has been traced to chromosomal, anatomic, hormonal and immunologic factors while half of the cases remain idiopathic. Aims: This study aimed to investigate the association of interleukin-10 (IL-10) polymorphisms with RM amongst the Indian population. Settings and Design: The present study included a total of 414 individuals including RM women (n = 199) with two or more pregnancy losses and healthy women (n = 215) without any previous history of pregnancy loss were taken as the control group. Materials and Methods: Demographic features and reproductive history of women with RM and healthy women were taken. Genotype analysis of IL-10 polymorphisms rs1800872 and rs1800896 was performed using the polymerase chain reaction (PCR) restriction fragment length polymorphism and amplification mutation refractory system PCR, respectively. Statistical Analysis Used: Student's t-test was used to compare the demographic features and reproductive history amongst both groups. Pearson's Chi-square was used to calculate the Hardy–Weinberg equilibrium, allelic and genotypic frequencies. All the statistical analyses were performed using the SPSS (version 21, IBM SPSS, NY, USA). Results: Our results suggested that the genotypic and allelic frequency of rs1800872 polymorphism did not differ significantly between RM cases and control women (P = 0.07 and P = 0.23, respectively). The GG genotype (P = 0.007) and G allele (P = 0.003) of rs1800896 were significantly associated with an increased risk of RM. A statistically significant difference was also found for the distribution of genetic models (dominant and co-dominant model) between both groups for rs1800896. However, haplotype analysis revealed that none of the haplotypes provides a risk for the progression of RM. Conclusion: The study is the first of its kind from our region and provides baseline data on the genetics of RM.